Not a Gentleman's War : An Inside View of Junior Officers in the Vietnam War - Milam, Ron (John R.) (Book collections on Project MUSE., 2009)
Debunking the view of the junior officer typified by Lt. William Calley of My Lai infamy, Milam, a combat veteran of the Vietnam War, demonstrates that most of the lieutenants who served in combat performed their duties well and effectively, serving with great skill, dedication, and commitment to the men they led. Milam's narrative provides a vivid, on-the-ground portrait of what the platoon leader faced: training his men, keeping racial tensions at bay, and preventing alcohol and drug abuse, all in a war without fronts. Yet despite these obstacles, junior officers performed admirably, as docu.